2021
DOI: 10.3389/fbioe.2021.787330
|View full text |Cite
|
Sign up to set email alerts
|

Post-Traumatic Osteoarthritis Assessment in Emerging and Advanced Pre-Clinical Meniscus Repair Strategies: A Review

Abstract: Surgical repair of meniscus injury is intended to help alleviate pain, prevent further exacerbation of the injury, restore normal knee function, and inhibit the accelerated development of post-traumatic osteoarthritis (PTOA). Meniscus injuries that are treated poorly or left untreated are reported to significantly increase the risk of PTOA in patients. Current surgical approaches for the treatment of meniscus injuries do not eliminate the risk of accelerated PTOA development. Through recent efforts by scientis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 116 publications
(97 reference statements)
1
3
0
1
Order By: Relevance
“…In fact, according to a 2020 epidemiological study of young adults, approximately 13% of patients with meniscus injury develop OA 18 years after injury. The 8-week-old rats used in this experiment are also common in the PTOA model, consistent with the age stage of young rats [ 17 , 18 ]. Currently, the treatment strategies for PTOA primarily aim to restore proper kinematic and biomechanical conditions and mitigate the inflammatory response.…”
Section: Discussionsupporting
confidence: 61%
“…In fact, according to a 2020 epidemiological study of young adults, approximately 13% of patients with meniscus injury develop OA 18 years after injury. The 8-week-old rats used in this experiment are also common in the PTOA model, consistent with the age stage of young rats [ 17 , 18 ]. Currently, the treatment strategies for PTOA primarily aim to restore proper kinematic and biomechanical conditions and mitigate the inflammatory response.…”
Section: Discussionsupporting
confidence: 61%
“…Previous biomechanical studies have shown that repairing the posterior root of the medial meniscus can restore the ability of the posterior root of the meniscus, absorb circumferential stress and reduce the contact pressure of the tibiofemoral joint, which is equivalent to that of the natural knee joint [11]. Unfortunately, meniscus repair of knee osteoarthritis has a higher progressive rate than the natural incidence of healthy knee [42]. An earlier cadaver study compared the contact mechanics of the tibiofemoral joint between anatomical and non-anatomical repair of the root tear.…”
Section: Discussionmentioning
confidence: 99%
“…Это регулярное (курсовое) введение ГлК, МСК и обогащенной тромбоцитами плазмы, аллогенная трансплантация хондроцитов, а также назначение симптоматических средств замедленного действия в терапии остеоартрита (Symptomatic Slow Acting Drugs for Osteoarthritis, SYSADOA), к которым относятся хондроитин, глюкозамин, диацереин, неомыляемые соединения авокадо и сои. Третий принцип -обязательное подключение немедикаментозных средств, продуманная фи-зическая и социальная реабилитация, что особенно существенно, поскольку большинство пациентов с ПТОА -лица молодого трудоспособного возраста, для которых крайне важно максимально полное и быстрое восстановление физической активности [48][49][50][51].…”
Section: реальная практикаunclassified